IMPLEMENTASI PEMBIASAAN ṢALAT BERJAMAAH SEBAGAI UPAYA MEMBENTUK AKHLAK MULIA SISWA DI SDIT AL MAQOM - Sarip Khoerul, - (2021)
Research conducted on the habit of praying in congregation is an innovation in character education which is an important thing to be held by educational institutions. With the background of the rampant deviations that occur among children and adolescents, it is hoped that the habituation of prayer can provide a positive role in fostering and educating students' character and can protect students from this deviant behavior. This study aims this is to practic the implementation of the customary implementation of congregational prayers at SDIT Al Maqom, find role for habituating congregational prayers at SDIT Al Maqom, find out the method and strategies for habituating congregational prayers at SDIT Al Maqom and find result for for habituating congregational prayers at SDIT Al Maqom . This research uses qualitative approach with descriptive method. Data collection using observation techniques, interviews, documentation and triangulation. Researchers found that the implementation of congregational prayer habituation with activities before and after as an approach method was already running according to planning, organizing, implementing, and controlling it. In addition, this program provides a good role for noble morals, including providing changes in behavior in terms of prayer habits, discipline, and responsibilities. Strategies carried out in the implementation of the ḍuha prayer to read the prayer is amplified and are usually divided into 2 places based on lower and upper class levels.